(NaWTOMATIZACIQ FIZI^ESKIH \KSPERIMENTOW (B:s [(NsBORNIK STATEJ(B] /s - (NpAJZIEW(B, (N|RBUTA p(B.s; (NiN(B-(NT \NERGETIKI I AWTOMATIKI an uZBEKSKOJ ssrs ((NtA[KENT (B:s (NfAN (B,s, 1991)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NaWTOMATIZACIQs; (NfIZI^ESKIJ \KSPERIMENTs